The Search for a Balance between the Principles of Freedom of Economic Activity and Environmental Protection in German Constitutional Law - Juškevičiūtė-Vilienė, Agnė (Teisė, 2024)
This paper examines how the Federal Republic of Germany, being one of the most powerful economies and a state with the highest sustainability ratings in the European Union, finds a balance between environmental protection requirements and economic freedom. The article focuses on the provisions of the Basic Law of the Federal Republic of Germany and the constitutional jurisprudence of the German Constitutional Court.
Keywords: economic freedom; environmental protection; constitution; Federal Republic of Germany; Constitutional Court